Da organização à crise do sistema integrado do transporte coletivo na grande Aracaju - Santos, Valdemir dos (2016)
Urban space in large metropolises worldwide is increasingly facing difficulties with the phenomenon of urban mobility, and collective public transport is still considered one of the best modalities to be used for this purpose. In Brazil it is no different, collective transportation is the major responsible for the displacement of the population of the large and medium urban centers and it is also responsible for the formation of the urban network from its routes formed by streets, avenues, arrivals and departure terminals, connecting various points of the cities. Over the years, it has been noticed that this transport, organized to promote urban mobility and the development of cities, has been facing a serious financial and structural crisis, reflecting directly on its users, as well as on the use of urban space. The municipalities of Aracaju, Nossa Senhora do Socorro, São Cristóvão and, more recently, Barra dos Coqueiros, have attracted attention with their collective public transportation systems, plunged in an unprecedented structural crisis. Upon that, this work had its motivation based on the problematic of the spatial dynamics that increasingly compromises the collective transportation system of Aracaju, which has come since its organization and is deepened with the crisis of urban mobility and the financial and structural crisis that the municipality has lived and, therefore, gave a new configuration to the geography of the metropolitan public transport of Aracaju. The aim of this dissertation is to organize the integrated public transport system within the limitations of the proposed scale, in the space and time trajectory of its last thirty years; evaluate the public policies implemented in that time frame; identify the elements that caused this crisis and its impacts on the daily life of the transportation user and; to verify the relationship between urbanization and the collective transportation offer in this region under the light of the urban mobility plan in the municipalities involved. The research is empirical analytical and has the critical analysis of qualitative and quantitative data as its method, with methodological procedures that were based on the bibliographical and documentary survey; field research with the obtaining of primary and secondary data through structured interviews and questionnaires with social actors who use of the transportation system; analysis and tabulation of the data collected during the research and; elaboration of thematic letters, charts, tables and final writing.